Tunable photoluminescence effect from ZnO films of Ag-decorated localized surface plasmon resonance by varying positions of Ag nanoparticles. (March 2019) - Huo, Chunqing; Jiang, Hua; Lu, Youming; Han, Shun; Jia, Fang; Zeng, Yuxiang; Cao, Peijiang; Liu, Wenjun; Wangying, Xu; Liu, Xinke; Zhu, Deliang
Graphical abstract: Highlights: For the ZnO films/Ag NPs (II) structure, oscillating electrons can be excited to higher energy level by LSP and transfer to the CB of ZnO, causing an enhanced PL intensity of NBE emission. For the Ag NPs (I)/ZnO films structure, electron transition to Fermi level of metal occurs at the MS interface due to the bending energy band that excites electrons to be close to the Fermi level of the metal, leading to a reduced PL intensity of NBE emission. The enhancement or reduction of luminescence intensity depends on the transport probability of electrons to the LSP level or to the Fermi level of the metal. The defect emission subsequently remained almost the same with weak LSP resonance coupling and energy mismatch in the structure. Abstract: By employing localized surface plasmon resonance (LSPR), the near band edge (NBE) emission intensity of ZnO films were greatly varied, while defect emission remained almost the same. This photoluminescence (PL) intensity enhancement or reduction is tunable by changing the position of Ag nanoparticles (NPs) relative to the ZnO films. The remarkable variation of the NBE emission was investigated deeply. These experimental results reveal that the Ag NPs play a key role in tuning the PL performance of the semiconductor material, where LSPR occurs.